New Farming as an Example of Social Innovation Responding to Challenges of Inner Mountain Areas of Italian Alps - Alessandro Gretter; Cristina Dalla Torre; Federica Maino; Andrea Omizzolo (Revue de Géographie Alpine)
Changes in the socio-economic framework that have taken place since the late 1960s have disrupted the multi-centennial balanced models of organisation in mountain communities, leading to a series of challenges in the socio-economical, cultural and environmental spheres. Mountain communities, independently or with the support of local and regional authorities, tried to halt or reverse these processes. In some cases, the effort is not only collective, but the sum of different individuals belonging or related to the community. Processes of social innovation arose sparsely in various alpine territories, and many of them are connected to a novel interest in the primary sector by locals and new residents. The combination of both, but not exclusively, could be considered as generating “new farming”. Authors present two cases identified in the north eastern part of the Italian Alps, which can be associated to this phenomenon. One has been analysed as an external initiative, in which the other authors were involved in supporting ongoing processes. Emerging common elements identified include multi-functionality, new job opportunities and profiles, more substantial social effects and the presence of a series of barriers. At present, actions and projects of social innovation, which are able to anticipate the changes and challenges of the future, seem to be inadequately addressed and deserve attention.